(untitled) (Jurnal Hortikultura Indonesia, 2021)
One of the main obstacles in mangosteen cultivation is a relatively long juvenile period due to the lack of root formation during seedling phase. To solve this problem, an effort was done by administering growth regulators, such as by applying shallot and tomato extracts which believed contain root growth regulator. This study aims to determine the effect of the shallot and tomato extracts on mangosteen seedling growth. This research was arranged factorially (3x2) using a randomized block design (RAK) with the treatment of three shallot extract in the concentrations (0 g L-1, 400 g L-1, and 800 g L-1), and tomato extract concentrations of 0 g L-1 and 100 g L-1 with three replication. The data were tested with analyses of variance and with LSD test at the 5% level. The results showed that shallot extract with a concentration of 400 g L-1 increased the stem diameter, fresh plant weight, and showed a tendency for the best treatment on the number of secondary roots. The application of tomato extract at 100 g L-1 increased plant weight, and there was an interaction effect between the provision of shallot extract and tomato extract on mangosteen leaf area. We recommend using either shallot extract solely at 400 g L-1 or tomato extract at 100 g L-1for better mangosteen seedling growth. Keywords: fresh weight, konsentration, organic matter, plant growth regulator